Bridging the information gap on cancer survivors in Europe: results from the iPAAC Joint Action. (30th September 2020) - De Angelis, R; Demuru, E; Rossi, S; Ventura, L; Baili, P; Bettio, M
Abstract: Background: Due to demographic transition cancer survivors are dramatically growing and challenging the sustainability of public health systems. Despite accurate indicators are increasingly needed for Health Technology Assessment and health care planning, population-based cancer prevalence is not systematically available in many countries. The European Joint Action "Innovative Partnership for Action Against Cancer" (iPAAC) aims at bridging this gap by supporting the inclusion of indicators on prevalence to complement the cancer burden statistics already available in the European Cancer Information System (ECIS). Methods: Analysis of a European-wide standardized dataset gathering information on 26 million patients from 100 cancer registries in 29 countries (EUROCARE-6). Methods to estimate and project complete and limited duration population-based prevalence indicators by demographic variables, cancer type and phase of care. Results: Cancer survivors are mostly women (about 55%) and people over-60 years. Highest crude prevalence proportions in women are observed for breast, colon-rectum, corpus uteri, skin melanoma and cervical cancer (from 1, 600 to 200 x 100, 000). Prostate, colon-rectum, bladder, non-Hodgkin lymphoma and skin melanoma were the most frequent cancers among male survivors (from 1, 000 to 200 x 100, 000). Between-country differences are wide, consistently with varying demographic structure, incidence and survival patterns. Impact of long-term survivorship strongly depends on disease lethality. Conclusions: Cancer survivors are a quite heterogenous population in respect of age, sex, cancer type and disease duration. Reliable and comparable prevalence indicators are essential to improve cancer care planning in European countries. Joint analysis of European wide population-based datasets strengthens the impact of cancer registries information and foster the release of complete statistics on cancer survivors. Key messages: Cancer survivors are a growing and heterogeneous population to be monitored in public health. Detailed and comparable indicators on cancer prevalence are proposed to complement the cancer burden statistics of the European Cancer Information System (ECIS) through improved collaborative efforts.